Exploring the Role of Social Media Use Motives, Psychological Well-Being, Self-Esteem, and Affect in Problematic Social Media Use - Schivinski, Bruno; Brzozowska-Woś, Magdalena; Stansbury, Ellena; Satel, Jason; Montag, Christian; Pontes, Halley M. (Frontiers in Psychology, 2020)
Given recent advances in technology, connectivity, and the popularity of social media platforms, recent literature has devoted great attention to problematic Facebook use. Exploring the potential predictors of problematic social media use beyond Facebook use has become paramount given the increasing popularity of multiple alternative platforms. In this study, a sample of 584 social media users (Mage = 32.28 years; 67.81% female) was recruited to complete an online survey assessing participants’ sociodemographic characteristics, patterns and preferences of social media use, problematic social media use (PSMU), social media use motives, psychological well-being, self-esteem, and positive and negative affect. Results indicated that 6.68% (n = 39) of all respondents could be potentially classed as problematic users. Moreover, analysis of results indicated that intrapersonal motive (β = .38), negative affect (β = .22), daily social media use (β = .18), surveillance motive (β = .12), and positive affect (β = -.09) each predicted PSMU. These variables accounted for about 37% of the total variance in PSMU, with intrapersonal motive driving the greatest predictive contribution, over and above the effects of patterns of SM use and sociodemographic variables. These findings contribute to the increasing literature on PSMU. The results of this study are discussed in light of the existing literature on PSMU.